The effectiveness of protecting citizens’ rights and freedoms by administrative courts in the Republic of Uzbekistan - Abdug‘affrova , Aziza (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article analyzes the effectiveness of administrative courts in protecting the rights and freedoms of citizens in the Republic of Uzbekistan from both theoretical and practical perspectives. It examines the role of administrative courts in resolving disputes between state bodies and citizens, ongoing judicial reforms, digitalization processes, and judicial practice. Additionally, a comparative analysis with foreign countries is conducted, and scientifically grounded proposals are put forward to further improve the administrative court system.